Design of Malaria Diagnostic Criteria for the Sysmex XE-2100 Hematology Analyzer (2010)
Abstract: Thick film, the standard diagnostic procedure for malaria, is not always ordered promptly. A failsafe diagnostic strategy using an XE-2100 analyzer is proposed, and for this strategy, malaria diagnostic models for the XE-2100 were developed and tested for accuracy. Two hundred eighty-one samples were distributed into Plasmodium vivax, P. falciparum, and acute febrile syndrome groups for model construction. Model validation was performed using 60% of malaria cases and a composite control group of samples from AFS and healthy participants from endemic and non-endemic regions. For P. vivax, two observer-dependent models (accuracy = 95.3–96.9%), one non–observer-dependent model using built-in variables (accuracy = 94.7%), and one non–observer-dependent model using new and built-in variables (accuracy = 96.8%) were developed. For P. falciparum, two non–observer-dependent models (accuracies = 85% and 89%) were developed. These models could be used by health personnel or be integrated as a malaria alarm for the XE-2100 to prompt early malaria microscopic diagnosis.